Effect of Transplanting Time and Cutting Size on Growth Parameters of Populus deltoids Under Nursery Conditions - Sourav Kumar; H. S. Saralch (International Journal of Economic Plants)
The present study was carried out at the Experimental area of Dept. of Forest and Natural Resources, Punjab Agricultural University, Ludhiana, Punjab, India during the year 2016-17. The study was conducted to know the suitable time of transplanting and cutting size and to evaluate the growth parameters of plants under nursery conditions. Two cutting sizes i.e. large 15 cm and small 10 cm  were used in the present investigation. First transplanting was done in the first week of May and second transplanting in the first week of June. The observations were recorded for various growth parameters of Populus deltoides under nursery conditions i.e. plant height, collar diameter, root length, root spread, shoot fresh and dry biomass. Cutting length had a pronounced significant effect on the growth parameters. It was observed that large cutting size exhibited significantly higher plant height (2.40 m), collar diameter (1.61), number of branches (7.44), root length (27.80 cm), root spread (612.36 cm2), shoot fresh biomass (558.89 g) and dry biomass (304.05 g) than the small sized cuttings. The values of various growth parameters i.e. plant height, collar diameter, number of branches, root length, root spread, shoot fresh and dry biomass were higher in the cuttings transplanted in the month of May in comparison to June. The interaction effect of time of transplanting×cutting size had non-significant effect on all the parameters except collar diameter and root spread where the results were found to be significant.